A Development of Single-phase Synchronous Inverter and Integration to Single-phase Microgrid effective for frequency stability enhancement. Issue 28 (2018) - Sekizaki, Shinya; Matsuo, Kosuke; Sasaki, Yutaka; Yorino, Naoto; Nakamura, Yuki; Zoka, Yoshifumi; Shimizu, Toshihisa; Nishizaki, Ichiro
Abstract: This paper develops a single-phase synchronous inverter (SSI) to stabilize a single-phase microgrid composed of static power conversion devices. The novel points in this paper are summarized as: (1) the proposed controller enables SSIs to implement directly a desired dynamic characteristic of synchronous machines, which is more advantageous than existing approaches in related works; (2) it can connect any single-phase systems; (3) an islanded single-phase microgrid without rotating machines can be stabilized by multiple SSIs. The proposed controller makes it possible to enhance the stability of microgrid facing network security and stability problems caused by increasing uncontrollable renewable energy sources and static power conversion devices with low inertia. The developed SSI realizes flexible use in the demand side operations under normal/faulted grid conditions. Hardware-in-the-loop (HIL) testbed including the proposed digital controller and the real-time simulator validates the effectiveness of the proposed controller in the experimental conditions.